Locus of control: an employee job embeddedness implication for bankers in Nigeria - Chijioke, Dibua Emmanuel; Ejiofo, Nwanmuoh Emmanuel; John-Akamelu, Chitom Racheal (goodwood publishing, 2020)
Purpose: This study examined the relationship between Locus of Control (LOC) and Employee Embeddedness (EE) in Nigeria's selected commercial banks. Research Methodology: The study adopted a survey research design with a population of 400 employees. The sample size was 190 was determined using Krejcie and Morgan formula. A questionnaire was the instrument for data collection, while the analysis was carried out using descriptive and inferential statistics. The hypothesis was tested at a 5% level of significance, Results: Internal LOC has a statistically significant effect on sacrifice (R = .976; R-Square = .952; p-value < 0.05). Internal LOC makes it possible for employees to be more entangled in the organization, thereby making exiting the firms more difficult. Limitations: Data was not collected from different regions in Nigeria, hence limiting the study's generalizability. Contribution: This study represents the most recent LOC work, and it is novel in relating LOC to EE in Nigeria. Keywords: Locus of Control, Internal LOC, Employee job embeddedness, Sacrifice